Decision Support System for Performance Assessment of Honorary Personnel Applying TOPSIS, SMART, and MAUT Methods with a Combination of ROC Weighting - Ricky Muharik; Rafi Luthfansyah; Vito Fajariyadi; Perani Rosyani; Resti Amalia (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research explores the assessment of honorary personnel performance through the application of the TOPSIS, SMART, and MAUT methods, along with ROC weighting. In today's competitive landscape, effective decision-making is vital for organizational success, and the role of Decision Support Systems (DSS) is emphasized. Unfair assessments can impact motivation and productivity, necessitating comprehensive criteria such as Work Discipline, Cooperation, and Education. The study employs TOPSIS, SMART, and MAUT, supported by ROC weighting, to holistically evaluate honorary personnel. The literature review provides insights into DSS and the methodologies used. The qualitative methodology involves literature review, problem identification, data collection, and method application. The findings highlight the dominance of certain alternatives in each method. The conclusion emphasizes the importance of method selection for accurate evaluation. Further study suggestions include exploring external validity, longitudinal impact, and qualitative research for a comprehensive understanding. This research aims to enhance organizational decision-making and improve the assessment of honorary personnel performance